Holonic self-sustainable systems for electrical micro grids - Ferreira, Adriano (2018)
The self-sustainability of micro grids is an important challenge in the smart grids field due to the need to balance the fast growing energy consumption, reduce greenhouse gas emissions and increase energy independence by using renewable resources. The use of decentralized paradigms, and particularly multi-agent systems and holonic control, enable to face this challenge by implementing intelligent mechanisms that allow an efficient management of the power flow. In this paper, a holonic based model is introduced, considering load scheduling and forecast mechanisms to improve the micro grids self-sustainability, and consequently reduce the energy cost and the energy dependency from the main utility. The designed holonic based model and strategies were developed by using the agent technology, and particularly the JADE framework, showing important improvements in the self-sustainability of micro grids working in different operating modes.